The Recognition of Our National Parks Among Young Adults - Éva Tóth (DETUROPE)
I conducted a survey questionnaire about the recognition of national parks among the students of the University of Pannonia, Georgikon Faculty in 2012 and 2013. According to my previous experience as a lecturer, I supposed that young people had incomplete knowledge about national parks. As the result of my previous survey about the Danube-Drava National Park Directorate, which is my narrower research area, I had the idea to test the knowledge of young people in a more general questionnaire in the hope of getting a more favourable picture. In order to prove my hypothesis I conducted a survey questionnaire among the students of the Georgikon Faculty who had not met this topic in their university studies yet. 132 students took part in the survey. The research revealed that although young adults had much better knowledge about national parks in general than about one particulate directorate, the results can be improved. According to the results the order of the recognition of national parks can be determined among young people. Young adults like hiking and going on outings in nature but they do not prefer taking part in the programs organized by the national park directorates.